2016
DOI: 10.5539/ijef.v8n12p120
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Relationship between Oil Prices and Stock Markets

Abstract: This paper investigates the relationship between oil prices and stock market returns for the G7 and the BRIC countries for the period 1991-2016 using cointegration and a vector error correction model. Results reveal that there is no long-run relationship between oil prices and the stock market indices of the G7 countries. However, they also reveal that there is a long-run relationship between oil prices and the stock market indices of three out of the four BRIC countries (Brazil, China and Russia). This result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The current article is relevant to some other articles that investigate corporate share-holding under the prism of the SEO/TTF timing. In this frame, some articles (Choie, 2016;Markoulis & Neofytou, 2016) targeted on the information asset and stock-taking intelligence of corporate investors, while others (Hao, 2014;Baker, Stein, & Wurgler, 2003) targeted the trading strategies and plans, but in both cases no TTF information was given. Gibson, Safieddine, and Sonti (2004) report that seasoned equity and option SEO initiatives, with the bigger boost in corporate share-holding, are detected between the (relative to SEO/TTF, SEO timing) quarters −1 and +1; these long-term investors reported that their positions outperform in the subsequent the SEO issue year and qualify this outperform to their competitive convenience asset position.…”
Section: Relevant Scholarship Descriptionmentioning
confidence: 99%
“…The current article is relevant to some other articles that investigate corporate share-holding under the prism of the SEO/TTF timing. In this frame, some articles (Choie, 2016;Markoulis & Neofytou, 2016) targeted on the information asset and stock-taking intelligence of corporate investors, while others (Hao, 2014;Baker, Stein, & Wurgler, 2003) targeted the trading strategies and plans, but in both cases no TTF information was given. Gibson, Safieddine, and Sonti (2004) report that seasoned equity and option SEO initiatives, with the bigger boost in corporate share-holding, are detected between the (relative to SEO/TTF, SEO timing) quarters −1 and +1; these long-term investors reported that their positions outperform in the subsequent the SEO issue year and qualify this outperform to their competitive convenience asset position.…”
Section: Relevant Scholarship Descriptionmentioning
confidence: 99%
“…Similarly, other surveys show that oil shocks do not influence stock market returns in either a positive or negative way. Another study indicated that oil price has no long-term impact in the G7 countries as it does in emerging economies like Brazil, Russia, India, and China (BRIC) states (Markoulis & Neofytou, 2016). The unrelated results can be explained by the different degree of dependence on oil in various economies.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics indicate the high interdependence rates between crude oil prices and the stock market returns in the 1990s (Markoulis & Neofytou, 2016). This correlation is associated with the influx in the housing market which influenced the Organization of the Petroleum Exporting Countries (OPEC) to stimulate oil production.…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, some articles (Choie, 2016;Markoulis & Neofytou, 2016) targeted on the information asset and stock-taking intelligence of corporate investors, while others (Hao, 2014;Baker, Stein, & Wurgler, 2003;Gibson, Safieddine, & Sonti, 2004) targeted on the trading strategies, tactics and plans, but in both cases no TTF information was given.…”
Section: Motivation and Previous Literaturementioning
confidence: 99%